The iconography of St Eugenia of Rome in medieval Spain and France - Znorovszky, Andrea-Bianka (Ikon;Rijeka, 2021;Band 14 (2021), Seite 165-176, 2021)
This article explores the visual and textual representation(s) of St Eugenia of Rome, a cross-dressed saint, as reflected in Spanish and French source material. It builds on previous interpretations in stating that these representations underscore the saint’s womanhood. The chapter also highlights the indispensable contribution that workshops made in generating local iconographies, which were connected to a wider international circulation of patterns and models.
Keywords: Eugenia; Heiligenvita; Heiligenbild